Effect of Technological Process and Temperature on Phospholipids in Buffalo Milk, Whey and Buttermilk - Marika Di Paolo; Valeria Pelizzola; Lucia De Luca; Loriana Casalino; Giulia Polizzi; Milena Povolo; Raffaele Marrone (Foods)
Phospholipids (PLs) are a group of biomolecules found in the milk fat globule membranes (MFGMs). Recently, MFGM phospholipids have attracted increasing amounts of attention due to their unique composition, stability, and potential health benefits, including protective effects against Alzheimer’s disease, hypercholesterolemia, and certain types of cancer. Although buffalo milk is the second most commonly produced milk and has high nutritional value, few studies have focused on the properties of buffalo MFGM. This study investigates the PLs composition of buffalo milk and related dairy by-products (whey and buttermilk). Milk and whey were collected from two dairy farms (A—small and B—big) to produce mozzarella buffalo cheese (high-pasteurization milk for GDO production and low for local); while buttermilk was obtained from a butter-making farm. Phospholipids were purified by a solid-phase extraction method and then identified by high-performance liquid chromatography with an evaporative light-scattering detector (HPLC/ELSD). Five classes of phospholipids [phosphatidylcholine (PC), phosphatidylethanolamine (PE), phosphatidylinositol (PI), phosphatidylserine (PS), and sphingomyelin (SM)] were identified. The thermal process of milk did not significantly affect the PLs milk. However, local whey showed a higher concentration of total PLs than GDO, which was mainly represented by PE followed by PC content. Farm A exhibited higher PL content than B, particularly with a greater concentration of SM. Buttermilk showed the lowest PLs content. These findings offer valuable insights for the dairy industry and related applications, contributing to the valorization of buffalo dairy products.